STRATEGI GURU DALAM MENGOPTIMALKAN KECERDASAN MAJEMUK DI SEKOLAH DASAR - Robiatul Munajah; Asep Supena (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2021)
The success of students in learning does not only depend on their own abilities. Several factors that can give effect need to be optimized. The teacher's strategy is very meaningful to optimize students' multiple intelligences according to the indicators that each student has. Every child in this world has various intelligences in different levels and indicators. This shows that all children, by nature, are intelligent. The difference lies in the level and indicators of intelligence. These differences are determined by various factors. One of them is the stimulation given when children learn in the learning process carried out by the teacher. The difference in intelligence among students demands a fair and existential way of thinking of educators. This research is a literature review to see more specifically the teacher's strategy in optimizing multiple intelligences in elementary schools based on research reference sources and books. Good educators are able to detect children's intelligence by observing the behavior, tendencies, interests, ways and qualities of children when reacting to the given stimulus. All indicators of intelligence can be recognized by educators to then make a profile of intelligence. Therefore, every teacher should know how to develop the intelligence of their students, by identifying each indicator of children's intelligence and realizing the importance of developing all the intelligences of their students.